The benzoyl-CoA pathway serves as a genomic marker to identify the oxygen requirements in the degradation of aromatic hydrocarbons - Godínez-Pérez, Camila Monserrat; Loza, Antonio; Hurtado, Juan Manuel; Gutiérrez-Ríos, Rosa-María (Frontiers in Microbiology, 2024)
The first step of anaerobic benzoate degradation is the formation of benzoyl-coenzyme A by benzoate-coenzyme A ligase (BCL). The anaerobic route is steered by benzoyl-CoA reductase, which promotes benzoyl-CoA breakdown, which is subsequently oxidized. In certain bacteria at low oxygen conditions, the aerobic metabolism of monoaromatic hydrocarbons occurs through the degradation Box pathway. These pathways have undergone experimental scrutiny in Alphaproteobacteria and Betaproteobacteria and have also been explored bioinformatically in representative Betaproteobacteria. However, there is a gap in our knowledge regarding the distribution of the benzoyl-CoA pathway and the evolutionary forces propelling its adaptation beyond that of representative bacteria. To address these questions, we used bioinformatic procedures to identify the BCLs and the lower pathways that transform benzoyl-CoA. These procedures included the identification of conserved motifs. As a result, we identified two motifs exclusive to BCLs, describing some of the catalytic properties of this enzyme. These motifs helped to discern BCLs from other aryl-CoA ligases effectively. The predicted BCLs and the enzymes of lower pathways were used as genomic markers for identifying aerobic, anaerobic, or hybrid catabolism, which we found widely distributed in Betaproteobacteria. Despite these enhancements, our approach failed to distinguish orthologs from a small cluster of paralogs exhibiting all the specified features to predict an ortholog. Nonetheless, the conducted phylogenetic analysis and the properties identified in the genomic context aided in formulating hypotheses about how this redundancy contributes to refining the catabolic strategy employed by these bacteria to degrade the substrates.